(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the content, structure, and pedagogical logic of work aimed at developing communicative skills in children with stuttering-related speech impairment within inclusive educational settings. The study is grounded in the understanding that stuttering is not only a disruption of speech fluency, but also a factor that may affect social participation, emotional regulation, classroom interaction, and the child’s confidence in verbal communication. In this context, communicative development is treated as a multidimensional process that includes speech initiation, dialogic participation, turn-taking, expressive clarity, listening behavior, situational language use, and interactional resilience. The article systematizes the main directions of intervention work, including diagnostic assessment of communicative difficulties, creation of psychologically safe speech environments, gradual expansion of verbal activity, integration of play-based and collaborative tasks, and coordination between speech therapist, teacher, and family. Particular attention is given to the pedagogical conditions that support communicative growth in children who experience speech tension, avoidance behaviors, or fear of speaking. The article also outlines principles for selecting educational content and communicative exercises according to age, individual speech profile, and classroom context. The proposed approach is oriented toward inclusive education practice and teacher preparation, emphasizing functional communication, emotional support, and sustainable participation in learning interactions rather than fluency-focused correction alone.